THE ROLE OF LAW IN FACING GLOBAL TRANSFORMATION OF THE ECONOMIC FIELD (Dinamika Hukum & Masyarakat, 2020)
AbstractThe history of people and state of Indonesia has been scarred dynamic seem as a complex life phenomenon That’s  the all might god procession. Time running without caring to profit or loss interest, supply and demand, good or bad. To anticipate the progress of free tradeactivities, it’s better to realize the own potency and ability strongly, such as cooperation , tourism, small and  medium enterprises. Those sector should be managed systematically and consistenly, supported by available protectable  norms, and prepared human developmentas business actor in which global business oriented for national purposes. To face this free trade era should be arraised The Newest Indonesia program such as the concept stated by Kotler. Key Words:  Glogal Transformation, Law needs, Economy.